PRACTICAL APPLICATION OF ENTERPRISE ARCHITECTURE, STUDY CASE OF SME METALMECHANIC IN MEXICO - Menchaca, Alicia G. Valdez; Lebrun, Carlos Vega; Benitez, Elías Olivares; Garcia, Juan C.Perez; Garza, Orlando Arzola; Martinez, Olga M. Preciado; Alvarado, Sergio R. Castaneda (European Scientific Journal, ESJ, 2014)
Small and Medium Enterprises are important in the world economy, according to statistics have a low level of survival and are facing serious problems like access to financing, weak management capacity, poor information about market opportunities, new technologies and methods of work organization and limited information about access to innovation and research funds. These firms have opportunity areas in the integration of its key processes into information and communication technologies; the methodology of Enterprise Architecture can provide them a model of integration supported with strategic planning. Integrated by partials architectures like business, applications and technology; each partial architecture has components that differ from each other. The architecture has been designed with the data of the firm of the study case resulting in the identification of strategic changes supported by the methodology, assessment of option for change and a change plan for the adoption of the methodology in their processes. This paper is the practical application of the architecture, result of two year of research in mediums enterprises ending with the designing and implementing in the study case.